KAJIAN PSIKOLOGI DALAM SINETRON ASMARA GEN Z SUTRADARA VEMMY SAGITA TAYANG DI SCTV (TEORI GUSTAV JUNG) - Dina Maharani; Nur Lailiyah; Marista Dwi Rahmayantis (Jurnal PENEROKA, 2026)
This study aims to describe the intrinsic elements and personality structure of the characters in the television series Asmara Gen Z, directed by Vemmy Sagita, based on Carl Gustav Jung's analytical psychology theory. The study falls within the scope of literary studies, particularly literary psychology, with a focus on analyzing characters and their personalities through an audiovisual medium. Asmara Gen Z was selected because it represents various psychological and social issues experienced by Generation Z adolescents, including identity exploration, family conflicts, social pressure, and interpersonal relationship dynamics. This study employed a descriptive qualitative method, with data consisting of dialogues, scenes, and characters' behaviors presented throughout the series. Data were collected through observation and note-taking techniques and analyzed by classifying, coding, interpreting, and describing them according to the research categories. Data validity was ensured through methodological and theoretical triangulation. The findings reveal that the intrinsic elements, including theme, plot, setting, and characterization, are closely interconnected in constructing the psychological dynamics of the characters. The identified personality structures consist of consciousness, the personal unconscious, the collective unconscious, the archetypes of persona and shadow, as well as the attitudes of introversion and extraversion. The findings further indicate that introversion and extraversion are the most dominant personality attitudes, while the persona and shadow archetypes most frequently influence the characters' inner conflicts and decision-making processes. These findings suggest that identity exploration, social pressure, and the need for social acceptance constitute the most prominent psychological characteristics of Generation Z as represented in the television series.